Heterogeneous graphene oxide membrane for rectified ion transport. Issue 3 (3rd January 2019) - Fei, Wenwen; Xue, Minmin; Qiu, Hu; Guo, Wanlin
Abstract : We demonstrate heterogeneous GO membranes with highly rectified ion transport and employ molecular dynamics simulations to reveal ion behavior. Abstract : Ion transport in nanoconfinement has drawn significant attention due to its crucial role in the functioning of biological nanochannels and in the stimulation of applications including iontronics, biosensing and energy conversion. Graphene oxide (GO) membranes that contain abundant two-dimensional nanochannels formed in-between stacked GO nanosheets are particularly attractive because they offer high tunability in terms of channel dimensions and surface properties. However, because of the inherent homogeneity of the GO membrane, ion transport through such nanochannels typically exhibit ohmic behaviour, inhibiting its potential widespread applications. Herein, we demonstrate heterogeneous GO membranes for a voltage-driven ion transport. The membrane is composed of a negatively-charged GO and a positively-charged PEI-grafted GO laminate. Highly rectified ion transport are observed through such membranes. Molecular dynamics simulations are employed to reveal micro-processes of ion behaviours in the two-dimensional nanochannels of the heterogeneous membranes. Furthermore, an enhancement of rectification performance is achieved when charge asymmetry of nanochannels is strengthened by adjusting the pH conditions of the electrolyte solutions. Our study should provide a potential paradigm for the application of GO membranes in ion transport control and the use as ionic rectifiers.